Given
x → 0 lim x p sin ( 5 x ) 3 tan 2 x − 3 sin 2 x = q
for some nonzero p , q , find 1 2 0 ( p + q ) .
This is a part of the College Calc problem set. You can find more problems here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x → 0 lim x p sin ( 5 x ) 3 tan 2 x − 3 sin 2 x = x → 0 lim x p ⋅ 5 x ( 3 tan x − 3 sin x ) ( 3 tan x + 3 sin x ) = x → 0 lim x p ⋅ 5 x ⋅ ( 3 tan 2 x + 3 tan x 3 sin x + 3 sin 2 x ) 2 3 x ( 3 tan x − 3 sin x ) ( 3 tan 2 x + 3 tan x 3 sin x + 3 sin 2 x ) = x → 0 lim x p ⋅ 5 x ⋅ 3 3 x 2 2 3 x ( tan x − sin x ) = x → 0 lim x p ⋅ 5 x ⋅ 3 3 x 2 2 3 x ⋅ tan x ( 1 − cos x ) = x → 0 lim x p ⋅ 5 x ⋅ 3 x 2 / 3 2 ⋅ x 1 / 3 ⋅ x ⋅ 2 1 x 2 = x → 0 lim 1 5 x p x 5 / 3 = q
Since q = 0 , we have p = 5 / 3 and thus q = 1 / 1 5 . Therefore, 1 2 0 ( p + q ) = 2 0 0 + 8 = 2 0 8 .
P.S. I would love someone to try and solve the entire thing with l'hopital.
I WA the problem ~~
By taylor expanding the function sin ( 5 x ) 3 tan 2 x − 3 sin 2 x , we get 1 5 x 3 5 + 2 7 0 7 9 x 3 1 1 + 4 8 6 0 0 4 2 6 4 7 x 3 1 7 + 1 8 3 7 0 8 0 0 4 3 0 0 6 5 9 x 3 2 3 + O ( x 3 2 5 ) which leads us to choosing p = 3 5 and q = 1 5 1 .
Problem Loading...
Note Loading...
Set Loading...
Claim: x → 0 lim x n + 2 tan n x − sin n x = 2 n , ∀ n ∈ R Proof: x → 0 lim x n + 2 tan n x − sin n x = x → 0 lim x n + 2 tan n x ( 1 − cos n x ) = x → 0 lim x n tan n x ⋅ x 2 1 − cos n x = x → 0 lim x n tan n x ⋅ x → 0 lim x 2 1 − cos n x = 1 ⋅ x → 0 lim d x d ( x 2 ) d x d ( 1 − cos n x ) = x → 0 lim 2 x n cos n − 1 x sin x = x → 0 lim 2 n cos n − 1 x ⋅ x → 0 lim x sin x = 2 n
In the above problem, n = 3 2 . So the limit is, q = x → 0 lim x p sin ( 5 x ) tan 3 2 x − sin 3 2 x = x → 0 lim x 3 8 tan 3 2 x − sin 3 2 x ⋅ x p ⋅ 5 x sin ( 5 x ) ⋅ 5 x x 3 8 = 2 3 2 ⋅ 5 ⋅ x → 0 lim 5 x sin ( 5 x ) x → 0 lim x 3 5 − p = 3 1 ⋅ 5 1 x → 0 lim x 3 5 − p Since q is non-zero, 3 5 − p = 0 ⟹ p = 3 5 ⟹ q = 1 5 1
Therefore, 1 2 0 ( p + q ) = 1 2 0 ( 3 5 + 1 5 1 ) = 2 0 8